Fabrication of 2D metal–organic framework nanosheet@fiber composites by spray technique. Issue 57 (28th June 2019) - Zhang, Liying; Chen, Huan; Bai, Xiaojue; Wang, Sha; Li, Linlin; Shao, Lei; He, Wenxiu; Li, Yunong; Wang, Tieqiang; Zhang, Xuemin; Chen, Junyi; Fu, Yu
Abstract : The feasible and rapid spray technique has been applied to fabricate 2D MOF nanosheet@fiber with homogeneous dispersion and high coverage. Abstract : A feasible and rapid one-step strategy has been developed to fabricate 2D metal–organic framework nanosheet (MOF-NS)@fiber composites at room temperature by spray technique, through which five kinds of MOF-NS@fiber were successfully prepared. The representative nanoscale CuBDC were synthesized on the surface of carbon fibers with homogeneous dispersion and high coverage.